SIFAT FISIK DAN MEKANIK KAYU MAHANG (Macaranga hypoleuca (Reichb.f.et Zoll.) M.A) YANG DIPADATKAN BERDASARKAN LAMA PENGUKUSAN DAN BESARNYA SUHU KEMPA - Sailana, Gerson Eliezer; Usman, Fadillah H.; Yani, Ahmad (Universitas Tanjungpura, 2014)
Common wood that used as a building material perceived increasingly difficult to obtain now. Therefore the need for efforts to overcome this condition partly by utilizing low quality wood (IV-V) like Mahang (Macaranga hypoleuca (Reichb.f.et Zoll.) M.A) in which quality can be improved by densification. There are two factors that have conducted in this research, first is steam time (40 minutes, 60 minutes and 80 minutes) and second one is temperature felts (160oC, 180oC and 200oC). Samples was made from Mahang beam with dimension is 30 cm (L) x 8 cm (W) x 4 cm (H), steamed in autoclave with temperature 120oC and hot pressed with a 30% target thicknes, the pressure felt 60 kg/cm2. Physical and mechanical process was conducted based on British Standard Methods No.373 (1957). The measured parameters are physical properties (moisture content, density and dimensional changes) and mechanical properties (MOE, MOR and MCS). Experimental designed that use in this research is 3x3 Factorial Experimental Design in a Completely Randomized Design with 3 replications. As the results of the research show that densification Mahang wood was improve the physical and mechanical properties. This research also showed that best densified treatment is 60 minute steamed with temperature felt 180oC. Keywords : Macaranga hypoleuca (Reichb.f.et Zoll.) M.A, densification, physical and mechanical.